Oligohydramnios is an independent risk factor for perinatal morbidity among women with pre-eclampsia who delivered preterm. (3rd June 2019) - Rabinovich, Alex; Holtzman, Keren; Shoham-Vardi, Ilana; Mazor, Moshe; Erez, Offer
Abstract: Purpose: The purpose of this study is to determine the relationship between oligohydramnios and adverse maternal and neonatal outcomes in a unique cohort of preterm pre-eclamptic patients. Materials and methods: A retrospective matched case–control study comparing 81 preterm parturients (28 0/7 and 36 6/7 weeks) with pre-eclampsia and oligohydramnios to 81 preterm pre-eclamptic patients with a normal amniotic fluid index (AFI). Results: About 4.8 percent of all our preterm pre-eclamptic patients had oligohydramnios. Patients in the study group showed a trend toward being older than 35 years (18.5%% versus 27.2%) and were more likely more likely to be primi-parous, and have previously delivered a small for gestational age (SGA) or a dead fetus ( p = .012, .039, and .032). Severity of pre-eclampsia, including HELLP and eclampsia as well as gestational age at delivery did not differ statistically between the study groups ( p = .47, .516). Growth restricted fetuses were more common in the study group ( p < .001) but oliguria was more prevalent in patients without oligohydramnios ( p = .046). Post-partum complications, pre-eclampsia during the puerperium, admission to intensive care units, and MgSO4 treatment were more common in the control group ( p = .028, .012, .008). But study group patients had more cesarean sections ( p = .011). Neonates of study group parturients had lower fetal weight, were more likely to be SGA, and experience fetal distress during labor ( p = .001, .001, and .03). Following delivery, they were more likely to have anemia and stay longer in neonatal intensive care unit (NICU) ( p = .017, .017). A multivariate logistic regression analysis showed that oligohydramnios, but not the severity of pre-eclampsia, significantly affected Composite Neonatal Outcome Apgar scores at 1 & 5 min (<5 and <7, respectively), neonatal death, umbilical cord pH <7.1, fetal distress (category III fetal heart rate tracing), fetal anemia, fetal hypoglycemia. Conclusions: Oligohydramnios is an independent risk factor for early neonatal morbidity in preterm pre-eclamptic patients. AFI <5 cm can be used as one component in the educated decision for delivery of these patients. Brief rationale The significance of oligohydramnios in pregnancies complicated by preterm delivery, preeclampsia or both is controversial. By comparing two relatively large, almost similar, cohorts of preterm preeclamptic parturient with and without oligohydramnios we demonstrated that Amniotic Fluid Index <5 cm is associated with a significant neonatal morbidity. This question was not previously addressed in proper manner aside one, much smaller, study that was under powered to address this topic. We innovate by illustrating the significance of oligohydramnios and its association with subsequent neonatal morbidity. Thus, we conclude that the presence of oligohydramnios in women with preterm preeclampsia can be a factor in the decision for or against conservative management of these patients.